Sufi Interpretive Patterns in Indonesian Quranic Exegesis - Hasanah, Maulida Rizqa; Suratman, Junizar (El-Rusyd, 2026)
This research is motivated by the many patterns of interpretation. Viewed from a historical perspective, Sufi interpretation is a manifestation of the spiritual seriousness of people who are clean, sincere and clear-hearted to interpret and reflect on the intentions of Allah SWT. in His word. Sufi interpretation is defined as a method or form of interpreting the verses of the Quran that is different from its apparent meaning because of the implied instructions. This study aims to discuss the patterns of Sufi interpretation in Indonesia by explaining several sub-chapters, namely; the meaning of Sufism and Sufism, the history of the development of Sufism and Sufism in Indonesia, Sufism in the Quran, the pattern of Sufism in the study of interpretation (Sufi interpretation), and Sufi interpretation figures. The method used is qualitative with a library research approach. After conducting research, the results were obtained that the pioneer of Sufism was Hamzah Fansuri. Holistically, the characteristic forms of Sufistic interpretation are divided into two, namely Isyari and Nazhari interpretations. However, among Indonesian tafsir scholars who are also experts in the field of Sufism, none of them wrote their tafsir books using Sufistic styles in the form of Isyari or Nadzari. This is because they separate the science of Sufism from the science of interpretation. So that in writing their interpretations, they still adhere to the meaning of zahir and the rules of interpretation that apply in general.